PROFILE OF PATIENTS WITH URINARY TRACT STONE AT UROLOGY DEPARTMENT OF SOETOMO GENERAL HOSPITAL SURABAYA IN JANUARY 2016-DECEMBER 2016 - Kurniawan, Reza; Djojodimedjo, Tarmono; Rahayu, Anny Setijo (Indonesian Urological Association, 2020)
Objective: To identify the profile of patients with urinary tract stones at the Urology Department of Soetomo General Hospital Surabaya in January 2016-December 2016. Material & methods: This was descriptive retrospective research conducted at the Urology Department of Soetomo General Hospital Surabaya. The data were obtained from medical records of patients diagnosed with urinary tract stone, with the amount of data collected was 62. The variables included were age, gender, address, main complaint, type and location of urinary tract stone. Results: The ratio of male:female among patients with urinary tract stone is 33:29. Most of the patients with urinary tract stone were aged 46-60 years old (52%), came with the main complaint of flank pain (79%), had the uric acid type of urinary tract stone (48%), and had urinary tract stone located at the kidneys (65%). Conclusion: Profile of patients with urinary tract stone at the Urology Department of Soetomo General Hospital Surabaya is as following: Ratio of male:female among patients with urinary tract stone is 33:29. Most of the patients with urinary tract stone were aged 46-60 years old, came with the main complaint of flank pain, had the uric acid type of urinary tract stone, and had urinary tract stone located at the kidneys.